MENINGKATKAN KETERAMPILAN SOSIAL SISWA MELALUI MODEL STAD PADA PEMBELAJARAN IPS DI SMPN 1 GUNUNG TIMANG KABUPATEN BARITO UTARA KALIMANTAN TENGAH - Apel Yuntun Kanadi (JURNAL SOCIUS, 2016)
The purpose of the research is to improve the Students Social Skills through STAD Model, Knowing The Implementation of STAD Model on increasing the Students Social Skills, and Knowing the Response of Students towards STAD Model on learning IPS. The steps of STAD Model consist of a Class Presentation, Working Group/Team, Quiz, Individual Progress Scores and Recognition Team. This is done because of Students Social Skills are very important to develop on Teaching and Learning Process in Schools so it would be used in the future on social life of the students.The study is planned in 2 cycles which include Planning, Implementation, Observations/Data Collection and Reflection. Classroom Action Research was conducted in VIIIB Class of SMPN 1 Gunung Timang, Barito Utara Regency ofCentral Kalimantan. Data collection methods include Observation, Student Worksheet, Test, Field Notes and Documentation. Analysis Data Technique consists of Validation Data and Interpretation of Qualitative Data.The result of this research showed that based on the data observation sheet of Student Social Skill in cycle I (3,27) is good criteria and cycle II (3,36) is also of good criteria. Based on observation of Student Social Skills on cycle I, that is, cooperation includes turn-taking/sharing, respecting/honoring, assisting/helping. Self Control consists of obeying instructions and controlling emotions. Sharing ideas and experiences include expressing ideas and receivingopinions increase in cycle II. Student Response in Cycle I (91,03%) is good and on the cycle II (95%) is also good.It is concluded that the STAD model can improve the Students Social Skills, the Implementation of STAD model on Learning IPS is good and Students Response on taking part in STAD model learning is also good.Key Word : Social Skills, STAD Model and Social Studies. Tujuan penelitian adalah meningkatkan Keterampilan Sosial Siswa melalui model STAD, Mengetahui Implementasi Model STAD dalam meningkatkan Keterampilan Sosial Siswa dan Mengetahui Respon Siswa terhadap Model STAD dalam Pembelajaran IPS. Langkah-langkah Model STAD terdiri dari Presentasi Kelas, Kerja kelompok/Tim, Kuis, Skor Kemajuan Individual dan Rekognisi Tim. Hal ini dilakukan karena Keterampilan Sosial Siswa sangat perlu di bentuk dalam Proses Belajar Mengajar di Sekolah sehingga berguna kelaknya dalam kehidupan sosial siswa. Penelitian direncanakan dalam 2 siklus yaitu meliputi Perencanaan, Pelaksanaan, Pengamatan/Pengumpulan Data dan Refleksi. Penelitian Tindakan Kelas dilaksanakan di Kelas VIIIB SMPN 1 Gunung Timang, Kabupaten Barito Utara, Kalimantan Tengah. Metode Pengumpulan Data meliputi Observasi, Lembar Kerja Siswa, Tes, Catatan Lapangan dan Dokumentasi. Teknik Analisis Data terdiri dari  Validasi dan Interpretasi data Kualitatif. Hasil Penelitian menunjukkan bahwa berdasarkan data lembar observasi Keterampilan Sosial Siswa siklus I (3,27) kriteria baik dan pada siklus II (3,36) kriteria baik. Berdasarkan hasil pengamatan Keterampilan Sosial Siswa pada siklus I yaitu Kerjasama meliputi bergiliran/berbagi, menghargai/menghormati, membantu/menolong, Kontrol Diri meliputi mengikuti petunjuk dan mengontrol emosi, Berbagi Ide dan Pengalaman meliputi menyampaikan pendapat dan menerima pendapat mengalami peningkatan pada siklus II. Respon Siswa pada Siklus I (91,03 %) baik dan pada siklus II (95 %) baik. Disimpulkan bahwa model STAD dalam Pembelajaran IPS dapat meningkatkan Keterampilan Sosial Siswa, Implementasi Model STAD dalam Pembelajaran IPS sudah baik serta Respon Siswa dalam mengikuti Pembelajaran model STAD juga sudah baik.Kata Kunci: Keterampilan Sosial, Model STAD dan IPS